Effect of Dried Lemongrass Leaves (Cymbopogon citrates) Powder on Haemato-biochemical Parameters in Broilers - Saraswat, Abhishek; Joshi, Monika; Shende, K. A.; Arora, Sunil; Gaurav, Abhishek; Amit (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from July to September, 2024 at the poultry farm of the College of Veterinary and Animal Science, Navania, Vallabhnagar, Udaipur, Rajasthan, India to evaluate the effect of dried lemongrass leaves (Cymbopogon citratus) powder on haemato-biochemical parameters in broilers. A feeding trial of six weeks followed by a metabolism trial was conducted using ninety-six-day-old chicks. The chicks were randomly distributed in a completely randomized block design in four treatment groups, viz., the T1 group, i.e., the control group fed on a basal diet; the T2 group, i.e., the basal diet+lemongrass leaves powder @ 5 g kg-1 feed; the T3 group, i.e., the basal diet+lemongrass leaves powder @ 10 g kg-1 feed; and the T4 group, i.e., the basal diet+lemongrass leaves powder @ 15 g kg-1 feed respectively in basal pre-starter, starter and finisher ration. There was a non-significant (p>0.05) difference in blood hemoglobin, PCV, TEC, TLC, serum globulin, A/G ratio, blood glucose, creatinine, ALT, and AST levels. Cholesterol level was significantly (p<0.05) high in the T1 group, whereas serum albumin and total protein levels were significantly higher (p<0.01) in the T4 group, and serum triglyceride level was significantly (p<0.01) higher in the T1 group as compared to other groups. It was concluded that supplementing the broiler diet with lemongrass leaves powder @ 15 g kg-1 feed could be beneficial for improving broiler chick haemato-biochemical parameters.